1999
DOI: 10.1038/sj.cdd.4400580
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal protection and destruction by NO

Abstract: Nitric oxide (NO)-related species include different redox states of the NO group, which have recently been reported to exist endogenously in biological tissues including the brain. The importance of these different NO-related species is that their distinct chemical reactivities can influence the life and death of neurons in response to various insults. In the case of NO + equivalents (having one less electron than NO . ), the mechanism of reaction often involves Snitrosylation or transfer of the NO group to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
142
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(146 citation statements)
references
References 38 publications
2
142
0
2
Order By: Relevance
“…NO, produced in the organism by a family of NO synthases (NOS), has been implicated in the regulation of blood pressure, immunity, and neurotransmission (Bredt and Snyder, 1994;Nathan and Xie, 1994;Stamler, 1994;Garthwaite and Boulton, 1995). It is also critically involved in many pathological responses, such as in¯ammation, septic shock, and neurotoxicity (Gross and Wolin, 1995;Nicotera et al, 1999;Lipton, 1999). Furthermore, NO can aect cell division, programmed cell death, or acquisition of dierentiated phenotype (Peunova and Enikolopov, 1995;Kuzin et al, 1996;Enikolopov et al, 1999;Papapetropoulos et al, 1997;Poluha et al, 1997;Ishida et al, 1997;Mannick et al, 1997;Forrester et al, 1996;Messmer and Brune, 1996;Brune et al, 1998;Gibbs and Truman, 1998;Wingrove and O'Farrell, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO, produced in the organism by a family of NO synthases (NOS), has been implicated in the regulation of blood pressure, immunity, and neurotransmission (Bredt and Snyder, 1994;Nathan and Xie, 1994;Stamler, 1994;Garthwaite and Boulton, 1995). It is also critically involved in many pathological responses, such as in¯ammation, septic shock, and neurotoxicity (Gross and Wolin, 1995;Nicotera et al, 1999;Lipton, 1999). Furthermore, NO can aect cell division, programmed cell death, or acquisition of dierentiated phenotype (Peunova and Enikolopov, 1995;Kuzin et al, 1996;Enikolopov et al, 1999;Papapetropoulos et al, 1997;Poluha et al, 1997;Ishida et al, 1997;Mannick et al, 1997;Forrester et al, 1996;Messmer and Brune, 1996;Brune et al, 1998;Gibbs and Truman, 1998;Wingrove and O'Farrell, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the long lasting eects of NO may be related to its ability to act as a potent regulator of proliferation: exogenously added NO can reversibly suppress DNA synthesis and progression through the various phases of the cell cycle (Stamler, 1994;Garg and Hassid, 1990;Lepoivre et al, 1990;Kwon et al, 1991), and can induce or suppress programmed cell death in particular cell types (Nicotera et al, 1999;Lipton, 1999;Mannick et al, 1997;Brune et al, 1998). It has been further speculated that part of the action of NO as a signaling molecule re¯ects its highly reactive nature and its potential, at high concentrations, to modify and damage DNA Tamir et al, 1996); however, the relevance of this feature of NO to its action in vivo is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In inflammatory pathological conditions, the increased production of nitric oxide and superoxide boosts the generation of reactive oxygen and nitrogen species, including peroxynitrite (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Peroxynitrite is a strong oxidant formed by the diffusion-limited reaction of superoxide and nitric oxide (11,12).…”
mentioning
confidence: 99%
“…Consistent with our studies evidence for redox regulation of caspase functions has been recently reported. For example, nitric oxide-mediated oxidation and S-nitrosylation of active site cysteine have been implicated in inhibition of caspase-3 activity (Lipton, 1999;Mohr et al, 1997). Depletion of cellular glutathione levels enhances the apoptotic e ect of TNF-a in certain hepatoma cells (Pierce et al, 2000).…”
Section: Discussionmentioning
confidence: 99%